Improvement of Food Packaging-Related Properties of Whey Protein Isolate-Based Nanocomposite Films and Coatings by Addition of Montmorillonite Nanoplatelets - Schmid, Markus; Merzbacher, Sarah; Brzoska, Nicola; Müller, Kerstin; Jesdinszki, Marius (Frontiers in Materials, 2017)
In the present study the effects of the addition of montmorillonite (MMT) nanoplatelets on whey protein isolate (WPI)-based nanocomposite films and coatings were investigated. The main objective was the development of WPI-based MMT-nanocomposites with enhanced barrier and mechanical properties. WPI-based nanocomposite cast-films and coatings were prepared by dispersing 0 % (reference sample), 3 %, 6 %, 9 % (w/w protein) MMT, or, depending on the protein concentration, also 12 % and 15 % (w/w protein) MMT into native WPI-based dispersions, followed by subsequent denaturation during the drying and curing process. The natural MMT nanofillers could be randomly dispersed into film-forming WPI-based nanodispersions, displaying good compatibility with the hydrophilic biopolymer matrix. As a result, by addition of 15 % (w/w protein) MMT into 10 % (w/w dispersion) WPI-based cast-films or coatings, the oxygen permeability (OP) was reduced by 91 % for glycerol-plasticized and 84 % for sorbitol-plasticized coatings, water vapor transmission rate (WVTR) was reduced by 58 % for sorbitol-plasticized cast-films. Due to the addition of MMT- nanofillers the Young’s modulus and tensile strength improved by 315 % and 129 %, respectively, whereas elongation at break declined by 77 % for glycerol-plasticized cast-films. In addition, comparison of plasticizer type revealed that sorbitol-plasticized cast-films were generally stiffer and stronger, but less flexible compared glycerol-plasticized cast-films. Viscosity measurements demonstrated good processability and suitability for up-scaled industrial processes of native WPI-based nanocomposite dispersions, even at high nanofiller-loadings. These results suggest that the addition of natural MMT- nanofillers into native WPI-based matrices to form nanocomposite films and coatings holds great potential to replace well-established, fossil-based packaging materials for at least certain applications such as oxygen barriers as part of multilayer flexible packaging films.